The Position of the Stock Exchange as a Self-Regulatory Organization in Capital Market Activities Based on Law Number 8 of 1995 Concerning Capital Markets - Yulia Putri Maulina; I Ketut (al-Afkar, Journal For Islamic Studies, 2025)
The capital market is a financial market for long-term funds. The capital market has an important role in a country's economy because the capital market functions as a means for business funding and a means for companies to obtain funds from the investing public (investors). Funds obtained from the capital market can be used for business development, expansion, additional working capital and so on. In the world of capital markets, there is a self-regulatory organization (SRO), which is an organization that regulates the capital markets sector. One form of SRO is the stock exchange. The stock exchange is a forum or meeting point between brokers and resellers to carry out securities buying and selling transactions (shares and bonds. This research will discuss the position of the stock exchange in capital market activities and its mechanisms. dividend distribution on the stock exchange.